Discursos e práticas de gestão em uma empresa do setor têxtil de Minas Gerais - Luiz Alex Silva Saraiva (2001)
In the current reality, the investment in productive technology already is not enough as in the past. The applied technology to the productive process needs to be associated to metamorphoses in a more including dimension the management. This aspect uses sophisticated elements to guarantee that in organizational level the capitalism continues getting success, either as for the performance, either as form of domination in the organization. The speech starts being used as one of the main components of management, having, however, gaps between what it is spoken and what really happens in organizational practices. With intention to analyze the relations between organizational speech andmanagement practices, this study it has as counterpoints of a side the globalization and the productive restructuring, and its new challenges to the organizations, specially related to the management; of another one, the Brazilian culture, that has strong influence of local organizations management, preserving traditional values. Inserted in a qualitative research strategy, data were collected in two phases, being the first a document analysis produced for the studied company and the second one research realized between September of 1999 and January of 2000, in which 39 people were interviewed (15 managers and 24 workers), in three units of a textile company of Minas Gerais. The main results disclose a dynamics complex, in which frequently speech is absorbed by workers of a partial, therefore, different form of organization intentions. This happens because the workers perception regarding the existingdiscrepancies between speech and management. practices However, instead of such gaps to constitute a minus aspect, fortify the company in a reality of weakness of the workers. Thus, even so it has divergences, the accomplishment of this study is a promising starting point towards other ones regarding as the management models explore organizational variables in all its potentialities, as the example of the relation of the workers with the company. The found gaps, in an organization that is in a side archaic, in an other innovative, as its surrounded environment, can be an interesting opportunity for the analysis on the possibility of local ways of management development.